Aspectos motivacionais e a redistribuição de cargos: um estudo na universidade federal do Amapá - SOUZA, Eliete Monteiro de (Universidade Federal do Amapá, 2022)
Far from administrative regulations, especially of a legal nature, the forms and strategies of public management development go through the motivation of public servants and the turnover of specialized labor. In this sense, considering motivation as the subjective interest to perform an action with variable intensity and that, therefore, it generates an impact on the quality of services offered, we sought to analyze the motivational aspects that involve the processes of Redistribution of servers linked to Marco Zero Campus of the Federal University of Amapá (UNIFAP). To reach the objectives established in the study, a qualitative approach was chosen, with a descriptive approach, and field research with the use of questionnaires. The total number of 200 servers was considered for the analysis, among administrative technicians and professors. The results pointed to the need for greater investments in terms of management of the motivation of the servers.